2019
DOI: 10.3390/app9245420
|View full text |Cite
|
Sign up to set email alerts
|

β-Caryophyllene: A Sesquiterpene with Countless Biological Properties

Abstract: β-Caryophyllene (BCP), a natural bicyclic sesquiterpene, is a selective phytocannabinoid agonist of type 2 receptors (CB2-R). It isn’t psychogenic due to the absence of an affinity to cannabinoid receptor type 1 (CB1). Among the various biological activities, BCP exerts anti-inflammatory action via inhibiting the main inflammatory mediators, such as inducible nitric oxide synthase (iNOS), Interleukin 1 beta (IL-1β), Interleukin-6 (IL-6), tumor necrosis factor-alfa (TNF-α), nuclear factor kapp a-light-chain-enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
82
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 186 publications
(116 citation statements)
references
References 83 publications
(128 reference statements)
1
82
0
3
Order By: Relevance
“…As described in our study, β-caryophyllene, the bicyclic sesquiterpene of J. procera EO was a promising mosquitocide against A. aegypti . These results are in a good accordance with the findings of many authors, where β-caryophyllene is proved as insecticide and repellant against pest insects ( de Elguea-Culebras et al., 2017 ; Francomano et al., 2019 ).…”
Section: Discussionsupporting
confidence: 92%
“…As described in our study, β-caryophyllene, the bicyclic sesquiterpene of J. procera EO was a promising mosquitocide against A. aegypti . These results are in a good accordance with the findings of many authors, where β-caryophyllene is proved as insecticide and repellant against pest insects ( de Elguea-Culebras et al., 2017 ; Francomano et al., 2019 ).…”
Section: Discussionsupporting
confidence: 92%
“…Orhan et al (2006) also reported the anti-inflammatory activity of the compound, while reviewing the synergistic effect of a-pinene with b-caryophyllene, as anti-inflammatory compounds. Interestingly, b-caryophyllene alone is a compound which has been demonstrated to possess a great potential application for various pathological conditions, as central nervous system diseases (Parkinson's disease, Alzheimer's disease), osteoporosis, cancer, and antibacterial (Francomano et al, 2019). Importantly, it is also approved as food additive, taste enhancer, and flavoring agent by U.S. Food and Drug Administration (FDA) and European Food Safety Authority (EFSA) (Fidyt et al, 2016;Machado et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…This compound is the only terpene known to interact with the body's endocannabinoid system (selectively binds to the CB 2 receptor) [57]. Caryophyllene has gastroprotective, analgesic, anticancerogenic, antifungal, antibacterial, antidepressant, anti-inflammatory, antiproliferative, antioxidant, anxiolytic, analgesic, and neuroprotective effects [58,59]. The presence of β-caryophyllene in many essential oils might contribute strongly to their antiviral ability.…”
Section: Entourage Effectmentioning
confidence: 99%